Eset - wielofunkcyjna roślina Etiopii i terminologia związana z nią - Gebru, Seifu (Investigationes Linguisticae, 2007)
The aim of this article is to present the Ethiopian plant ? Eset. Due to its many functions there is a vast terminology related to its cultivation, processing and application in everyday life. The first part, after the introduction explains how Eset is farmed and what are the names of parts of this plant and stages of its development. Next part shows how Eset serves as food in Ethiopia and what are the names of dishes based on Eset in Amharic language. Eset can also be used to produce some commodities ? strings, mattresses, mats and bowls. All vocabulary collected in this research is a result of author?s homeland education and personal communication with numerous informants who grow Eset. The important trait of Eset is an intergenerational tradition of its cultivation.